2004
DOI: 10.1016/j.physa.2003.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Do Pareto–Zipf and Gibrat laws hold true? An analysis with European firms

Abstract: By employing exhaustive lists of large firms in European countries, we show that the upper-tail of the distribution of firm size can be fitted with a power-law (Pareto-Zipf law), and that in this region the growth rate of each firm is independent of the firm's size (Gibrat's law of proportionate effect). We also find that detailed balance holds in the large-size region for periods we investigated; the empirical probability for a firm to change its size from a value to another is statistically the same as that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(125 citation statements)
references
References 37 publications
8
112
1
1
Order By: Relevance
“…al. [18] found that the Zipf law characterised the size distribution of about 260,000 large firms from 45 European countries during the years 1992-2001. A Zipf law implies that a majority of small firms coexist with a decreasing number of disproportionately large firms.…”
Section: Firm Size Distributionmentioning
confidence: 99%
“…al. [18] found that the Zipf law characterised the size distribution of about 260,000 large firms from 45 European countries during the years 1992-2001. A Zipf law implies that a majority of small firms coexist with a decreasing number of disproportionately large firms.…”
Section: Firm Size Distributionmentioning
confidence: 99%
“…We denote financial data (assets, sales, number of employees, and so forth) in year T and T + 1 as x T and x T +1 , respectively. Inverse symmetry denotes that joint PDF P J (x T , x T +1 ) is symmetric under the inverse exchange of variables x T ↔ x T +1 [23,24]:…”
Section: Inverse Symmetry Gibrat's Law and Non-gibrat's Lawmentioning
confidence: 99%
“…Interestingly, these short-term laws lead to a power-law and a lognormal distribu-tion observed at a point of a certain time. Under inverse symmetry, Gibrat's law and non-Gibrat's law respectively lead to power-law [23,24] and log-normal distribution [29]- [32]. Furthermore, under quasi-inverse symmetry, Gibrat's law and non-Gibrat's law respectively lead to a quasi-varying power-law and quasi-varying lognormal distribution [25,26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations